Machine learning in clarifying the coupled effects of pore structure and nitrogen density on desalination capacity for capacitive deionization - Hao Kong; Hongshan Wang; Ming Gao; Qi Li; Ran Li; Yuchen Kang; Weilong Xiao; Tianqi Ao; Haiyan Mou; Wenqing Chen (Desalination, 2026)

Bacterial surface interfaces in food systems: a programmable regulatory layer - Hao-Ran Zhang; Jun Meng; Yun-Peng Hao; Jing-Qian Song; Xiao-Yue Wang; Jing-Yi Yang; Zai-Chen Li; Jun Xi; Chang-He Ding; Tong Li (Trends in Food Science & Technology, 2026)

Limited role of continental arc in crustal growth: Insights from zircon U-Pb ages and Lu-Hf isotopes of late Paleozoic granitoid plutons from the northern North China Craton - Jing Ran; Hao Wang; Jin-Hui Yang; Jin-Feng Sun; Jing-Yuan Chen; Yu-Sheng Zhu (Lithos, 2026)

Macroscopic crack ratio as a structural surrogate linking linear filtration and nonlinear expression in sludge dewatering - Yi-Wen Yuan; Hao-Ran Chen; Zhi-Hao Liu; Shi-Yu Ren; Chang-Ji Huang; Raymond Jianxiong Zeng; Hou-Feng Wang (Process Safety and Environmental Protection, 2026)

Quantifying hydrological responses to climate change and associated canopy variability using an integrated LSTM-SWAT modeling framework - Kunhao Jiang; Hui Ran; Xinyi Chen; Yingnan Wei; Yuanxin Dai; Qiang Yu; Hao Feng; Xiaotao Hu; Ning Yao (Journal of Hydrology, 2026)

Ionic-network-regulated LiCl-confined hydrogel foams for solar-driven atmospheric water harvesting - Hao Kong; Qi Li; Ran Li; Yuchen Kang; Hongshan Wang; Jin Yu; Wenqing Chen; Tianqi Ao; Haiyan Mou (Chemical Engineering Journal, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Recent advances in therapeutic agents for uranium poisoning: a comprehensive review - Juan Li; Wenrun Li; Feng Huang; Qiuchi Wang; Hongjia Liu; Liyi Chen; Qiuping Wang; Yong Li; Shiyan Fu; Yazhen Zhao; Yonghong Ran; Yuhui Hao (BioMetals, 2026)

A lyophilized CHA–lateral flow platform for point-of-care detection of miR-106b-5p from L1CAM-Immunocaptured small extracellular vesicles in Alzheimer's disease - Ran Xu; Hao Chen; Chao Zhao; Xiqing Ding (Analytica Chimica Acta, 2026)

Probiotic Bacillus strains enhance cellulose digestibility and silkworms growth via gut microbiota modulation - Yueqin Jin; Ying Zhao; Chen Chen; Xueping Jiang; Sitong Chen; Ran Zhang; Hao Li; Zhongzheng Gui (Journal of Insect Physiology, 2026)

Impact of waste biomass binders on the pelletizing, combustion, and engineering feasibility of sludge–coal slime co-pelletized fuel - Hao-Ran Chen; Yi-Wen Yuan; Zhi-Hao Liu; Chang-Ji Huang; Shi-YuS Ren; Hou-Feng Wang; Raymond Jianxiong Zeng (Environmental Research, 2026)

Direct synthesis of non-migratory, intrinsically antioxidant ultra-high molecular weight polyethylene by nickel catalysis - Fei-Ran Yang; Wen-Bing Wang; Tian-Ming Yang; Hao-Xiang Sun; Quan Wang; Meng-He Xu; Jia-Wei Chen; Chen Zou (Chemical Engineering Journal, 2026)

Ambient PM2.5 exposure is associated with clear cell renal cell carcinoma aggressiveness and promotes tumor progression through ROS-mediated AKT/HIF-2α signaling - Xiao-Hui Wu; Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Xue-Peng Jin; Fei Lin; Qing-Shui Zheng; Yong Wei; Shao-Hao Chen; Ning Xu; Xue-Yi Xue (Chemico-Biological Interactions, 2026)

Screening and identification of soybean antioxidant peptides using Fe3O4-Modified carbon fibers - Xiao-Feng Chen; Xiang-Yu Huang; Hao-Ran Liu; Li Ding; Li Wen; Xu-Feng Wang; Zhou Xu; Yun-Hui Cheng; Mao-Long Chen (Food Bioscience, 2026)

Cation-size-directed interfacial and electronic engineering of Ti3C2Tx MXenes via ionic liquid intercalation for high-rate proton storage - Jeremiah Hao Ran Huang; Wei-Siang Lo; Yu-Ting Tai; Yu-Chun Shih; Hong-Kang Tian; I-Wen Peter Chen (Chemical Engineering Journal, 2026)

Hydrocarbon charging dynamics and its coupling with reservoir densification in a tight sandstone system: Insights from the Jurassic of the Yangxia Sag, Kuqa Depression - Chang-chao Chen; Jun Li; Jinz-hou Wang; Ling Li; Hao-ran Gao; Zheng-lian Pang; Xiu-yan Chen; Min Yang (Applied Geophysics, 2026)

Exogenous microbial agents interact with housefly larvae to reshape the microbiome and accelerate cellulose degradation in silkworm (Bombyx mori) excrement - Chen Chen; Yuanhao Zhang; Yueqin Jin; Jieling Zhou; Xueping Jiang; Sitong Chen; Ran Zhang; Hao Li; Zhongzheng Gui (Journal of Insect Physiology, 2026)

Lipid profile of sheep milk and its impact on taste: a combination study of lipidomics and electronic tongue - Hao Yuan; Zhongshi Zhu; Yuxin Wang; Chang Chen; Haozhan Liu; Ran Li; Liwei Zhang; Yuxuan Song (Food Research International, 2026)

Cellular copper overload mediates senescence-associated secretory phenotype induction in BV2 microglia following lead and copper exposure - Tao Wang; Chao Chen; Ran Li; Li-Hong Su; Hao-Jie Tian; Hui-Jing Wang; Jia-Yi Xiong; Qing Dai; Di Wu; Gang Zheng (Food and Chemical Toxicology, 2026)

The effect of high-pressure homogenization pressure on the 3D printing of potato protein secondary emulsion - Yi Liu; Hao-ran Chen; Ao-xue Qie; Chong-hao Bi; Zhi-gang Huang; Quan-lai Li; Qiu-yue Du (Food and Bioproducts Processing, 2026)

Construction of Li1-xMn2O4-Pb composite electrode ESIX system for efficient lithium recovery from high-sodium sulfate-type lithium-precipitation mother liquor - Jialu Chen; Jiang Gao; Ran Zhang; Zirui Wang; Qiang Ren; Fengfeng Gao; Zhonglin Zhang; Xiao Du; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2026)

Role and therapeutic potential of icariin in metabolic diseases - Anni Song; Ran Wei; Yang Yang; Haoshuang Li; Fengyi Chen; Yutong Pang; Xiaotong Ma; Shijie Hao (Inflammopharmacology, 2026)

Genome wide association analysis and association of genetic risk and lifestyle with upper gastrointestinal cancer among an endoscopy-screened cohort in China - Feifan He; Xianhui Ran; Hao Jiang; Zhiyuan Fan; Yueying Zhang; Jinwu Wang; Changqing Hao; Guohui Song; Yanwei Gong; Yanyan Li; Xinqing Li; Ru Chen; et al. (Science Bulletin, 2026)

Long-term capsaicin intake and gut inflammation: microbial alterations, metabolic mechanisms, and intervention effects - Liangliang Zhu; Yijia Chen; Jiayang Jin; Mengyao Zhao; Jingfang Ran; Hao Yin; Xiaoguo Ji; Liming Zhao (Food Research International, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

A multi-component recycling strategy for photovoltaic waste: Co-recovering silicon and PVDF into Ag–F reinforced Si/C anodes - Yihao Li; Yiqing Chen; Xiaojiao Zhang; Yaoguang Guo; Shuai Chen; Jie Yang; Tie Lin; Haodong Ran; Yang Zhang; Qin Xu; Yanlin Wu; Hao Yuan; et al. (Resources, Conservation and Recycling, 2026)

Strategy for optimization of auto-driven electrochemical module towards phosphorus recovery from wastewater: Performance and mechanism of electric field regulation - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Ying Chen; Qi Kuang; Yuan Liu (Journal of Cleaner Production, 2026)

Will technological innovation across carbon neutrality timelines increase asset stranding risks in China’s carbon-intensive sectors? - Bai-Chen Xie; Hao-Ran Wu; Bofeng Cai; Jian Su; Philip Kofi Adom (Journal of Industrial Ecology, 2026)

Physicochemical strategies for antibiotic removal in aquaculture wastewater: Mechanistic insights, technological challenges, and sustainable development pathways - Tai-Yue Wang; Yan-Ping Qiao; Kai-Jun Yue; Ming Cheng; Li-Ting Hao; Nan Zhang; Ran-Bin Liu; Chen Shi (Aquaculture, 2026)

Homo longi, Denisovans, Neanderthals and other archaic hominins in eastern Asia prior to the rise of Homo sapiens - Jingkun Ran; Huan Xia; Song Xing; Hao Li; Fahu Chen (Science Bulletin, 2026)

Integrative analysis of DEHP exposure and prostate cancer: Mechanistic insights and predictive modeling - Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Fei Lin; Shao-Hao Chen; Xiao-Dong Li; Xiong-Lin Sun; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Zhi-Bin Ke; Ning Xu (Environmental Pollution, 2026)

Rock failure mechanism and stability control of extraction roadways under extreme non-uniform pressure - Lei Fan; Ju-cai Chang; Hao-ran Chen (Applied Geophysics, 2026)

A multifunctional 5-fluorouracil prodrug: synthesis, biological evaluation, and antitumor mechanism investigation - Ran Zhang; Liqing Tang; Jianglong He; Guanyu Jiang; Yingfei Su; Xueping Jiang; Ping Wu; Dongyang Zhang; Sitong Chen; Hao Li; Zhongzheng Gui (Molecular Diversity, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Amorphous–nanocrystalline PdCuFe electrocatalyst enabling efficient ethylene glycol oxidation across a broad potential window - Ran Hao; Baoti Xu; Can Jin; Guifeng Liu; Zhaozhe Yang; Zupeng Chen; Kui Wang (Chemical Engineering Journal, 2026)

An optimal method for GNSS water vapor tomography based on parameter adaptation - Fei Yang; Ruixian Hao; Haoyu Wang; Lei Wang; Zhicai Li; Junxi Zheng; Yingying Wang; Ran Chen (GPS Solutions, 2026)

MHC II system of mandarin fish (Siniperca chuatsi): Gene identification, expression analysis and transcriptional regulation - Jing Hou; Lu Qi; Ran Cao; Lan Hao Liu; Shan Nan Chen; Pin Nie (Aquaculture, 2026)

Decoding electric vehicle adoption using XGBoost and SHAP analysis - Peng Chen; Xiankui Yang; Feng Hao; Ran Tao (Travel Behaviour and Society, 2026)

Towards zero liquid discharge: Resource recovery and circular economy pathways via bipolar membrane electrodialysis - Hao-Ran Yang; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Ying Chen; Yuan Liu (Chemical Engineering Journal, 2026)

Binder-free, in-situ inkjet-reduced graphene with tunable layer architectures for supercapacitor applications - Yu-Hsuan Ho; Jeremiah Hao Ran Huang; Jia-Yu Ji; I-Wen Peter Chen (Chemical Engineering Journal, 2026)

Liquid-like PDMS brushes/TiO2 microcapsule-driven coatings with integrated self-healing, photodegradation, and antifouling functions - Jingjing Ren; Taolin Zhang; Shouzheng Jiao; Fanghua Pan; Jingru Sun; Ran Mo; Yuwei Hao; Zhengyu Chen; Siqiao Zhang; Zhicheng Sun; Zhongjun Cheng (Journal of Environmental Chemical Engineering, 2025)

Optimizing housefly larval bioconversion of silkworm excrement through wheat bran Supplementation: Enhanced cellulose degradation and nutrient recovery - Chen Chen; Yuanhao Zhang; Xueming Xu; Xueping Jiang; Jieling Zhou; Jia Kong; Ran Zhang; Hao Li; Zhongzheng Gui (Journal of Asia-Pacific Entomology, 2025)

Multi-side-port nanotube array based on pillar[5]arene-Ag(I) self-assembly for efficient and recyclable separation of trace pyridine - Hao-Ran Yang; Jintao Tian; Xing Han; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

Flexible solar evaporator for simultaneous desalination and VOCs removal from seawater - Long-Feng Hu; Huiting Zhang; Huan Lin; Hui Niu; Hao-Ran Chen; Quan-Fu An (Chemical Engineering Journal, 2025)

Bifidobacterium animalis subsp. Lactis A6 alleviates comorbid constipation and depression by rebalancing tryptophan metabolism - Jian Wang; Yimei Ren; Juan Chen; Shanbin Chen; Xiaoxia Li; Jianwen Chen; Xifan Wang; Lijun Li; Liang Zhao; Yixuan Li; Qi Zhang; Wei Xiong; et al. (Science Bulletin, 2025)

Regulation of phytoplankton community by mesoscale eddies and the East Indian Coastal Current in the southwestern Bay of Bengal during the northeast monsoon - Hao Chen; Yuanli Zhu; Lihua Ran; Mengjia Zhang; Xiao Ma; Hongliang Li; Feng Zhou; W.N.C. Priyadarshani; Zhibing Jiang (Marine Environmental Research, 2025)

Machine learning decoding of electronic thresholds in prediction of oriented generation of solar-induced oxidative reactive species and antibiotics degradation - Hao Bi; Zhiruo Zhou; Qian Liu; Ran Zhao; Fangyuan Chen; Jun Zhang; Zhurui Shen (Journal of Hazardous Materials, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

A laser with instability reaching 4 × 10 - 17 based on a 10-cm-long silicon cavity at sub-5-K temperatures - Zhi-Ang Chen; Hao-Ran Zeng; Wen-Wei Wang; Han Zhang; Run-Qi Lei; Jian-Zhang Li; Cai-Yin Pang; She-Song Huang; Xibo Zhang (Science Bulletin, 2025)

The early Holocene vegetation history and quantitative reconstruction of climate in the Chahanur Lake, Inner Mongolia Plateau, China - Xu-Ran Zhang; Hua-Yong Zhang; Zhong-Yu Wang; Hao Chen; Xiao-Chang Wu; Zhao Liu (Palaeoworld, 2025)

LLTO-based electrodes for selective lithium extraction from high Mg2+/Li+ brines: Performance and mechanistic insights - Ran Zhang; Jialu Chen; Qian Xu; Beichen Sun; Xiao Du; Shanxia Luo; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2025)

Operational optimisation of domestic refrigerators based on user behaviour prediction and deep reinforcement learning - Hao-Ran Li; Wei Zhang; Qiang Chen (International Journal of Refrigeration, 2025)

Curcumin-mediated photodynamic treatment efficiently inhibits Bacillus cereus and extends the shelf-life of flat rice noodles - Hao-Ran Ji; Jia-Jun Yan; Zi-Hui Chen; Wen-Li Shi; Li-Wen Chen; Juan Wang; Yu Ding; Ai-Min Jiang; Bing Du; Cai-Hu Liao; Hong-Tao Lei; Quan Zhou; et al. (Food Research International, 2025)

Nitrogen cycling and ecological impacts mediated by water mass interactions in the Yangtze river estuary and the adjacent east China Sea: insights from nitrogen and oxygen isotopes - Ziying Zhou; Zhi Yang; Bin Wang; Haiyan Jin; Lihua Ran; Zhibing Jiang; Qianna Chen; Feng Zhou; Hao Zheng; Jianfang Chen (Continental Shelf Research, 2025)

Chemotaxis-driven Stenotrophomonas pavanii surface-aggregated FastPETase system for in situ degradation of PET microplastics - Si-Qi Chen; Qing-Song Huang; Yang Li; Hao-Ran Zhang; Yan Huang; Jing Wu; Sheng Chen; Zheng-Fei Yan (Chemical Engineering Journal, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Synergistic effects of environmental factors on benthic diversity: Machine learning analysis - Yiyang Feng; Mengyu Yang; Hao Chen; Kun Zhang; Fuju Ran; Ziyan Chen; Haijun Yang (Water Research, 2025)

Data-driven differentiable model for dynamic prediction and control in wastewater treatment - Yun-Peng Song; Wen-Zhe Wang; Yu-Qi Wang; Wan-Xin Yin; Jia-Ji Chen; Hao-Ran Xu; Hao-Yi Cheng; Fang Ma; Han-Tao Wang; Ai-Jie Wang; Hong-Cheng Wang (Water Research, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Machine learning-based prediction of desalination capacity of electrochemical performance of nitrogen-doped for capacitive deionization - Hao Kong; Ming Gao; Ran Li; Luwei Miao; Yuchen Kang; Weilong Xiao; Wenqing Chen; Tianqi Ao; Haiyan Mou (Desalination, 2025)

A versatile and double cross-linked hydrogel with potent antibacterial and immunomodulatory Zn@Met nanocomplexes for enhanced diabetic-infected wound healing - Tinglong Chen; Xueliang Zhang; Shengzhe Zhou; Dong Fang; Dinghao Luo; Zhaoyang Ran; Yingchun Liu; Cheng Xu; Jinhao Cao; Xiaodong Li; Yongqiaong Hao; Xiaoqing Wang; et al. (Chemical Engineering Journal, 2025)

Genomic and transcriptomic insights into the cellulose-degrading mechanism of Bacillus subtilis DC-11 and its novel cellulose catabolic pathway - Chen Chen; Minqi Zhang; Yuanhao Zhang; Xueping Jiang; Jia Kong; Jieling Zhou; Gaiqun Huang; Ran Zhang; Hao Li; Zhongzheng Gui (Archives of Microbiology, 2025)

Near-complete recovery of phosphorus from fresh human urine: Combining magnesium-air fuel cells with modified granular attapulgite - Lin-Jiang Zhong; Lin-Feng He; Hao-Ran Yang; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Ying Chen; Xuan Zhao; Hong Liu; Yuan Liu (Journal of Environmental Management, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Selective preparation of aromatic compounds from catalytic pyrolysis polyester coating over Ni, Mo and Co metal modified ZSM-5 - Zhen-Qiang Yu; Yao-Xin Xiao; Dong Liang; Che Zhao; Zhen Huang; Gang-Qi Cheng; Rui Shan; Hao-Ran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Indian ocean-type mantle domain in the Carboniferous Qushiman ophiolite in the Northern Pamir: Significance for the intra-oceanic subduction in the Paleo-Tethys Ocean - Yan Jing; Chuan-Lin Zhang; Chen Wang; Masumeh Sargazi; Zhi-Hao Song; Yi-kang Quan; Zhi-Kai Xu; Xiao-Qiang Liu; Hong-Ran Wang (Chemical Geology, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Bed-immersion-ratio variation as an efficient strategy to regulate denitrification efficiency directionally in elemental sulfur packed-bed reactors - Guijiao Zhang; Hao-Ran Xu; Wenwei Liao; Jia-Min Xu; Na Zhang; Daheng Ren; Xinjie Chen; Wenyan Mao; Xiangli Zeng; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Evaluation of the nutritional quality of yeast protein in comparison to animal and plant proteins using growing rats and INFOGEST model - Xin Cao; Hongjuan Liu; Miao Yang; Kanmin Mao; Xinzheng Wang; Ziyu Chen; Mingqi Ran; Liping Hao (Food Chemistry, 2025)

In-situ electrochemical XRD and raman probing of ion transport dynamics in ionic liquid-etched Ti3C2Tx MXene for energy storage applications - Jeremiah Hao Ran Huang; Shih-Wen Tseng; I-Wen Peter Chen (Chemical Engineering Journal, 2025)

Study on the degradation performance of coking wastewater using an in-situ enhanced Fe2+/Fe3+ cycle dual-cathode Electro-Fenton system - Chengwang Zhao; Yufang Ran; Yao Gong; Chen Hong; Yi Xing; Yunxiao Sun; Hao Wang; Wei Ling; Yijie Wang; Weibo Feng; Jiachen Hou; Xinlin Zhai; et al. (Journal of Environmental Chemical Engineering, 2024)

Sustainable soil rehabilitation with multifunctional mandarin orange peel/tobermorite composite hydrogels: Water retention, immobilization of heavy metals, fertilizer release and bacterial community composition - Caiqing He; Xugang Wang; Haiyan Mou; Wenjing Hou; Qilu He; Yuchen Kang; Hao Kong; Ran Li; Wenqing Chen; Tianqi Ao; Shuanjun Li; Jian Yang; et al. (Chemical Engineering Journal, 2024)

Demographic disparity and influences in electric vehicle adoption: A Florida case study - Ran Tao; Xiankui Yang; Feng Hao; Peng Chen (Transportation Research Part D: Transport and Environment, 2024)

Different responses of individuals, functional groups and plant communities in CSR strategies to nitrogen deposition in high-altitude grasslands - Xueqi Li; Ying Li; Hao Shen; Shuai Li; Zhenzhen Zhao; Jiannan Xiao; Ran Zhang; Hang Shi; Hui Zuo; Tu Danjia; Guoming Chen; Xueli Zhou; et al. (Science of The Total Environment, 2024)

MdAP2-like, a new regulator in apple, simultaneously modulates fruit softening and size - Miaomiao Wang; Wenduo Zhan; Ming Chen; Yanfei Guo; Hao Wang; Yao Wu; Tuanhui Bai; Jian Jiao; Chunhui Song; Jiangli Shi; Ran Wan; Kunxi Zhang; et al. (Postharvest Biology and Technology, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

Solvation structure manipulation of ester-based electrolyte by acetonitrile additive enables high-capacity and stable K-storage for phenazine-based anode - Xiaokang Chu; Ran Chen; Hang Chen; Hao Wang; Luanjie Nie; Haobo Xia; Qingxue Lai; Zixia Lin; Mengtao Ma; Hao Gong; Jing Zheng (Chemical Engineering Journal, 2024)

Delaying cyclization of polyacrylonitrile by boric acid for sulfurized poly(acrylonitrile) cathode materials - Xuan Zhang; Hui-Chao Lu; Chen-Ran Hao; Ji-Qiong Liu; Xi-Rui Kong; Jiu-Lin Wang (Chemical Engineering Journal, 2024)

Reconciled estimation of Antarctic ice sheet mass balance and contribution to global sea level change from 1996 to 2021 - Rongxing Li; Guojun Li; Gang Hai; Huan Xie; Yuan Cheng; Wei Chen; Xiangbin Cui; Minghu Ding; Chunchun Gao; Tong Hao; Changqing Ke; Chuanjin Li; et al. (Science China Earth Sciences, 2024)
The Antarctic Ice Sheet (AIS) has been losing ice mass and contributing to global sea level rise (GSLR). Given its mass that is enough to cause ∼58 m of GSLR, accurate estimation of mass balance trend is critical for AIS mass loss monitoring and sea level rise forecasting. Here, we present an improved approach to reconciled solutions of mass balance in AIS and its regions from multiple contributing solutions using the input-out, altimetric, and gravimetric methods. In comparison to previous methods, such as IMBIE 2018, this approach utilizes an adaptive data aggregation window to handle the heterogeneity of the contributing solutions, including the number of solutions, temporal distributions, uncertainties, and estimation techniques. We improved the regression-based method by using a two-step procedure that establishes ensembled solutions within each method (input-output, altimetry, or gravimetry) and then estimates the method-independent reconciled solutions. For the first time, 16 contributing solutions from 8 Chinese institutions are used to estimate the reconciled mass balance of AIS and its regions from 1996 to 2021. Our results show that AIS has lost a total ice mass of ∼3213±253 Gt during the period, an equivalent of ∼8.9±0.7 mm of GSLR. There is a sustained mass loss acceleration since 2006, from 88.1±3.6 Gt yr −1 during 1996–2005 to 130.7±8.4 Gt yr −1 during 2006–2013 and further to 157.0±9.0 Gt yr −1 during 2014–2021. The mass loss signal in the West Antarctica and Antarctic Peninsula is dominant and clearly presented in the reconciled estimation and contributing solutions, regardless of estimation methods used and fluctuation of surface mass balance. Uncertainty and challenges remain in mass balance estimation in East Antarctica. This reconciled estimation approach can be extended and applied for improved mass balance estimation in the Greenland Ice Sheet and mountain glacier regions.

Concentration and activation biresponsive strategy in one analysis system with simultaneous use of G4 structure-specific signal probe and enzyme-catalyzed reaction - Yu-Shu Li; Chun-Feng Feng; Hao-Ran Chen; Wei-Guo Yang; Fei Liu; Ming-Li Su; Ruo Yuan; Li-Qun Zhang; Wen-Bin Liang (Analytica Chimica Acta, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Characteristics of corn starch/polyvinyl alcohol composite film with improved flexibility and UV shielding ability by novel approach combining chemical cross-linking and physical blending - Hao-Nan Wei; Xin-Yue Liu; Chen-Chen Wang; Ran Feng; Bao Zhang (Food Chemistry, 2024)

Distribution characteristics of sulfonamide antibiotics between water and extracellular polymeric substances in municipal sludge - Ming Cheng; Chen Shi; Bo-Han Zhao; Tai-Yue Wang; Nan-Zhang; Ran-Bin Liu; Da-Qi Cao; Xiao-Di Hao (Environmental Research, 2024)

Progress toward adsorption mechanism exploration method for capacitive deionization: Experimental, mathematical model, computational chemistry and machine learning - Luwei Miao; Ming Gao; Weilong Xiao; Yuchen Kang; Ran Li; Hao Kong; Haiyan Mou; Wenqing Chen; Tianqi Ao (Desalination, 2024)

Whole Genome Sequencing Analysis of Cellulose-degrading Bacterium DC11 Isolated from Silkworm Excrement and Characterization of Its Key Cellulase Gene ytoP - Yuanhao Zhang; Hao Li; Minqi Zhang; Xueping Jiang; Chen Chen; Xiaohui Zhang; Ran Zhang; Gaiqun Huang; Gang Liu; Zhongzheng Gui (Journal of Asia-Pacific Entomology, 2024)

Electrolyte matching design for carboxylic acid-based organic K-storage anode - Jing Zheng; Hao Wang; Chi Hu; Hang Chen; Wanying Zhang; Xiaokang Chu; Luanjie Nie; Ran Chen; Jianying Long; Meng Lei; Jijian Xu; Zixia Lin; et al. (Chemical Engineering Journal, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

Involvement of CgHSFB1 in the regulation of self-incompatibility in ‘Shatian’ pummelo - Chenchen Liu; Xin Zheng; Jianbing Hu; Qiang Xu; Hao Wen; Zhezhong Zhang; Ran Liu; Xiangling Chen; Zongzhou Xie; Junli Ye; Xiuxin Deng; Lijun Chai (Plant Molecular Biology, 2024)

ML-Net: A Multi-Local Perception Network for Healthy and Bleached Coral Image Classification - Sai Wang; Nan-Lin Chen; Yong-Duo Song; Tuan-Tuan Wang; Jing Wen; Tuan-Qi Guo; Hong-Jin Zhang; Ling Mo; Hao-Ran Ma; Lei Xiang (Journal of Marine Science and Engineering, 2024)
Healthy coral reefs provide diverse habitats for marine life, playing a crucial role in marine ecosystems. Coral health is under threat due to global climate change, ocean pollution, and other environmental stressors, leading to coral bleaching. Coral bleaching disrupts the symbiotic relationship between corals and algae, ultimately impacting the entire marine ecosystem. Processing complex underwater images manually is time-consuming and burdensome for marine experts. To rapidly locate and monitor coral health, deep neural networks are employed for identifying coral categories, which can facilitate the automated processing of extensive underwater imaging data. However, these classification networks may overlook critical classification criteria like color and texture. This paper proposes a multi-local perception network (ML-Net) for image classification of healthy and bleached corals. ML-Net focuses on local features of coral targets, leveraging valuable information for image classification. Specifically, the proposed multi-branch local adaptive block extracts image details through parallel convolution kernels. Then, the proposed multi-scale local fusion block integrates features of different scales vertically, enhancing the detailed information within the deep network. Residual structures in the shallow network transmit local information with more texture and color to the deep network. Both horizontal and vertical multi-scale fusion blocks in deep networks are used to capture and retain local details. We evaluated ML-Net using six evaluation metrics on the Bleached and Unbleached Corals Classification dataset. In particular, ML-Net achieves an ACC result of 86.35, which is 4.36 higher than ResNet and 8.5 higher than ConvNext. Experimental results demonstrate the effectiveness of the proposed modules for coral classification in underwater environments.

A self-assembled 3D nanoflowers based nano-ELISA platform for the sensitive detection of pyridaben - He Chen; Li An; Meng Li; Hao Liu; Zhong Jin; Huan Ma; Jingwei Ma; Juan Zhou; Ran Duan; Di Zhang; Xiu Cao; Tieliang Wang; et al. (Food Chemistry, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Discovery of abundant shock-induced metallic lead nanograins in lunar zirconolite - Ai-Cheng Zhang; Hao-Xuan Sun; Tian-Ran Trina Du; Jia-Ni Chen; Li-Xin Gu (Geochimica et Cosmochimica Acta, 2024)

Soot particles formed by n-heptane and n-heptane/oxymethylene ether-3 in an inverse diffusion flame: A comparative analysis of chemical features - Ye Liu; Ran Zhang; Jun Wang; Yajun Wang; Gang Lv; He Yang; Haibo Chen; Tiezhu Li; Bin Hao; Junhua Guo (Fuel, 2024)

Effects of dietary bacterial culture of fengycin-producing Bacillus subtilis on growth performance, intestinal and hepatopancreas health, intestinal microbiota and disease resistance of common carp (Cyprinus carpio) - Rui Xia; Shenghui Li; Hongwei Yang; Yajie Zhao; Tsegay Teame; Qiang Hao; Mingxu Xie; Min Li; Qile Chen; Chunling Song; Chao Ran; Yalin Yang; et al. (Aquaculture, 2024)

Influence of the community assemblage on sulfur distributions in the South China sea - Hao-Quan Zhang; Juan Yu; Jing-Guang Lai; Gui-Peng Yang; Long-Fei Liu; Yu Jiang; Xin-Ran Song; Yong-Qiao Chen; Hou-Jin Zhou; Qi Zhang (Marine Environmental Research, 2024)

Unravelling solvation structure and interfacial mechanism of pyrrolidinium-based ionic liquid electrolytes in potassium-ion batteries - Xiaokang Chu; Hao Wang; Chi Hu; Qingxue Lai; Luanjie Nie; Hang Chen; Ran Chen; Zixia Lin; Mengtao Ma; Jing Zheng (Chemical Engineering Journal, 2024)

Excellent energy storage performance of lead-based antiferroelectric ceramics via enhancing dielectric breakdown mechanism - Jian Zhou; Zisheng Xu; Huilin Yang; Limin Chu; Liming Chen; Hangren Li; Jianxiang Ding; Songlin Ran; Zhengming Sun; Xihong Hao (Chemical Engineering Journal, 2024)

Variations in the concentration, inventory, source, and ecological risk of polycyclic aromatic hydrocarbons in sediments of the Lake Chaohu - Hao-Ran Tian; Xi-Tao Zhang; Li-Li Zhao; Shu-Chuan Peng; Ji-Zhong Wang; Yi-Han Chen (Marine Pollution Bulletin, 2024)

An integrated numerical and analytical model to understand the effect of relative phase in a dual-port solid-state microwave heating process - Kartik Verma; Ran Yang; Hao Gan; Aly Fathy; Mark Morgan; Jiajia Chen (Journal of Food Engineering, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

Effects of nanoplastics exposure on ingestion, life history traits, and dimethyl sulfide production in rotifer Brachionus plicatilis - Juan Yu; Su Wang; Hao-Quan Zhang; Xin-Ran Song; Long-Fei Liu; Yu Jiang; Rong Chen; Qi Zhang; Yong-Qiao Chen; Hou-Jin Zhou; Gui-Peng Yang (Environmental Pollution, 2024)

Experimental and numerical study on shear behaviour of concrete-filled double-skin steel tubular structures - Ran Ding; Hao-hao Bai; Yun-lun Sun; Yan Chen; Jian-sheng Fan (Engineering Structures, 2024)

Exploration of risk analysis and elimination methods for a Cr(VI)-removal recombinant strain through a biosafety assessment in mice - Wanting You; Qiuying An; Dongbei Guo; Zebo Huang; Lulu Guo; Zigui Chen; Hao Xu; Guangshun Wang; Yeting Weng; Zhangye Ma; Xiaoxuan Chen; Feng Hong; et al. (Science of The Total Environment, 2024)

Study on characterization and distribution of four regions of tight sandstone condensate gas reservoirs in the depletion development process - Xiliang Liu; Hao Chen; Zhihai Chen; Ran Yang; Liyang Song; Mingxing Bai; Ping Qiu; Mingsheng Zuo; Borui Li; Baoxi Yang; Xuankai Jiang; Yuting Wu; et al. (Fuel, 2024)

Production of carbon nanotubes via catalytic pyrolysis of polyethylene over Ni/ZSM-5 prepared by ethylene glycol assisted impregnation - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Tao-li Huhe; Hao-Ran Yuan; Yong Chen (Fuel, 2024)

Effects of nitrogen application on physicochemical properties of rice starch under elevated temperature - Wenzhe Liu; Kailu Wang; Yufei Zhao; Yingying Shen; Chen Zhang; Yuxuan Peng; Xuan Ran; Hao Guo; Yanfeng Ding; She Tang (Food Chemistry, 2024)

A new cyclohexenone derivative from phomopsis sp. XM-01 - Cheng-Yao Wang; Dong Gan; Chen-Zhe Li; Li Zhu; Xiao-Ran Zhang; Ya-Ni Li; Xiu-Hong Wu; Hao Zhou; Le Cai (Natural Product Research, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

π-π Stacking constructing efficient charge channels for perovskite photovoltaics - Chun-Hao Chen; Fan Hu; Kai-Li Wang; Jing Chen; Tian-Yu Teng; Yi-Ran Shi; Yu Xia; Zhen-Huang Su; Xing-Yu Gao; Ilhan Yavuz; Zhao-Kui Wang; Liang-Sheng Liao (Science Bulletin, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Mitigating the adverse effect of warming on rice canopy and rhizosphere microbial community by nitrogen application: An approach to counteract future climate change for rice - Yingying Shen; Lei Xu; Hao Guo; Hashmi Ismail; Xuan Ran; Chen Zhang; Yuxuan Peng; Yufei Zhao; Wenzhe Liu; Yanfeng Ding; She Tang (Science of The Total Environment, 2023)

Pectolinarigenin attenuates hepatic ischemia/reperfusion injury via activation of the PI3K/AKT/Nrf2 signaling pathway - Hao Li; Yabin Chen; Mingjie Ding; Zhiping Yan; Wenzhi Guo; Ran Guo (Chemico-Biological Interactions, 2023)

Estimating water surface evaporation losses under floating coverage: Modeling and Application - Ke-Wu Han; Ke-Bin Shi; Xin-Jun Yan; Fei Ling; Guo-Chen Hao; Qian-Ran Qin (Journal of Hydrology, 2023)

Twelve natural estrogens and ten bisphenol analogues in eight drinking water treatment plants: Analytical method, their occurrence and risk evaluation - Zhao Tang; Ze-hua Liu; Hao Wang; Yi-ping Wan; Zhi Dang; Peng-ran Guo; Yu-mei Song; Sa Chen (Water Research, 2023)

Carbon nanotubes production from catalytic pyrolysis of polyethylene over nickel-based catalysts: The influence of support materials - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Hao-Ran Yuan; Yong Chen (Fuel, 2023)

Nitrogen fertilizer alleviates rice yield loss without increasing global warming potential under elevated temperatures - Yingying Shen; Kailu Wang; Yufei Zhao; Liqing Yang; Wenzhe Liu; Tongyang Yin; Xueqin Wang; Xuan Ran; Hao Guo; Yuru Ma; Xinying Wu; Yao Chen; et al. (Field Crops Research, 2023)

Interpretable bus energy consumption model with minimal input variables considering powertrain types - Hao Xu; Ran Tu; Tiezhu Li; Haibo Chen (Transportation Research Part D: Transport and Environment, 2023)

Alpha-ketoglutarate alleviates cadmium-induced inflammation by inhibiting the HIF1A-TNFAIP3 pathway in hepatocytes - Yinzhao Jia; Chuanzheng Yin; Wenbo Ke; Jing Liu; Bing Guo; Xiaofei Wang; Peng Zhao; Shaobo Hu; Chen Zhang; Xuan Li; Ran Liu; Xichuan Zheng; et al. (Science of The Total Environment, 2023)

Airborne PM2.5 pollution: A double-edged sword modulating hepatic lipid metabolism in middle-aged male mice - Renjie Hu; Lu Zhang; Li Qin; Hao Ding; Ran Li; Weijia Gu; Rucheng Chen; Yunhui Zhang; Sanjay Rajagoplan; Kezhong Zhang; Qinghua Sun; Cuiqing Liu (Environmental Pollution, 2023)

A new cyclopentenone derivative from Trichoderma atroviride HH-01 - Li Zhu; Jia-Peng Wang; Feng Hao; Dong Gan; Xiao-Ran Zhang; Chen-Zhe Li; Cheng-Yao Wang; Liang Zhang; Le Cai (Natural Product Research, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

Dietary pattern interfered with the impacts of pesticide exposure by regulating the bioavailability and gut microbiota - Ai Song Chen; Dong Hui Liu; Hao Nan Hou; Jia Ning Yao; Shou Chun Xiao; Xiao Ran Ma; Pei Ze Li; Qian Cao; Xue Ke Liu; Zhi Qiang Zhou; Peng Wang (Science of The Total Environment, 2023)

Repaired surface structural imperfection of tin Wide-Bandgap perovskite films for photovoltaic application - Tian-Yu Teng; Fan Hu; Yan-Hui Lou; Jun-Jie Cao; Chun-Hao Chen; Yi-Ran Shi; Kai-Li Wang; Jing Chen; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2023)

Intermittent ultrasound retains cellulases unlock for enhanced cellulosic ethanol with high-porosity biochar for dye adsorption using desirable rice mutant straw - Zhen Hu; Qian Li; Yuanyuan Chen; Tianqi Li; Youmei Wang; Ran Zhang; Hao Peng; Hailang Wang; Yanting Wang; Jingfeng Tang; Muhammad Nauman Aftab; Liangcai Peng (Bioresource Technology, 2023)

Clinical evaluation of efficacy of leflunomide combined with low-dose prednisone for treatment of myasthenia gravis - Xin Huang; Li Qiu; Yaru Lu; Jiaxin Chen; Wenhao Yang; Changyi Ou; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2023)

Shape-controlled fabrication of MnO/C hybrid nanoparticle from waste polyester for solar evaporation and thermoelectricity generation - Zifen Fan; Jiaxin Ren; Huiying Bai; Panpan He; Liang Hao; Ning Liu; Bingyu Chen; Ran Niu; Jiang Gong (Chemical Engineering Journal, 2023)

Identification of a major stable QTL for spikelet number in wheat (Triticum aestivum L.) and its genetic effects analysis on yield-related traits - Mingsu Cao; Jizi Dong; Hao Wang; Yibiao Cai; Tianhang Ma; Xiaohan Zhou; Jingguo Xiao; Shihui Li; Linqu Chen; Huiyuan Xu; Chunhua Zhao; Yongzhen Wu; et al. (Euphytica, 2022)

mTOR deletion ameliorates CD4 + T cell apoptosis during sepsis by improving autophagosome-lysosome fusion - Hao Wang; Guangxu Bai; Jianwei Chen; Wen Han; Ran Guo; Na Cui (Apoptosis, 2022)
Autophagy dysfunction contributes to CD4 + T cell apoptosis during sepsis leading to impairment of adaptive immunity. However, the underlying mechanism is unclear. The mammalian target of rapamycin (mTOR) pathway modulates CD4 + T cell survival during sepsis through mechanisms that are not fully understood. We developed a mouse model of sepsis through cecal ligation and puncture (CLP) to investigate dynamic changes in autophagy in CD4 + T cells. We used T cell specific-mTOR/tuberous sclerosis complex 1 (TSC1)-knockout mice to explore the roles of the mTOR pathway in modulating autophagy during sepsis. We observed reduced fusion of autophagosomes with lysosomes in the CD4 + T cells of CLP mice, which may represent a characteristic feature of autophagy dysfunction. Deletion of mTOR relieved autophagosome-lysosome fusion dysfunction and ameliorated apoptosis of CD4 + T cells in CLP mice, but this rescued phenotype was abolished by treatment with bafilomycin A1, a specific A-L fusion inhibitor. We further explored the underlying molecular mechanism and found that phosphorylation levels of transcription factor EB were significant higher in CLP mice and that expression of A-L fusion protein SNAREs were restricted, both of which were ameliorated by mTOR deletion. Taken together, these results suggest that the mTOR pathway plays a critical role in regulation of CD4 + T-cell apoptosis during sepsis, partly through regulation of A-L fusion-related protein transcription.

Genome-wide association analysis of root length traits in Brassica napus at germination stage under sodium carbonate stress - Jindong Chen; Hao Zhang; Jiangqun Tong; Chunyue Liu; Jinghong Ran; Juan Tang; Jiaying Liu; Jing Wen; Changli Zeng; Heping Wan; Jinxiong Shen (Euphytica, 2021)

Carbon monoxide-triggered health effects: the important role of the inflammasome and its possible crosstalk with autophagy and exosomes - Rong-Jane Chen; Yu-Hsuan Lee; Tzu-Hao Chen; Yu-Ying Chen; Ya-Ling Yeh; Ching-Ping Chang; Chien-Cheng Huang; How-Ran Guo; Ying-Jan Wang (Archives of Toxicology, 2021)

Performances of six eupelmid egg parasitoids from China on Japanese giant silkworm Caligula japonica with different host age regimes - Yong-Ming Chen; Xing-Ran Qu; Tian-Hao Li; Asim Iqbal; Xingeng Wang; Zhi-Yong Ren; Nicolas Desneux; Lian-Sheng Zang (Journal of Pest Science, 2021)

Cerebellar Atrophy in Multiple System Atrophy (Cerebellar Type) and Its Implication for Network Connectivity - Hao Zhang; Shaozhen Ji; Shan Ren; Ming Liu; Weizheng Ran; Xinning Zhang; Wenyang Tian; Zhigang Chen; Zhiqun Wang (The Cerebellum, 2020)

Experimental investigation on the mechanical characteristics of gas-bearing coal considering the impact of moisture - Ming-yi Chen; Yuan-ping Cheng; Jing-chun Wang; Hao-ran Li; Ning Wang (Arabian Journal of Geosciences, 2019)

Characterization of polysaccharides purified from Lacquer tree seed cakes and its antioxidant activity - Hongxia Chen; Chengzhang Wang; Hao Zhou; Ran Tao; Jianzhong Ye; Wenjun Li (Natural Product Research, 2018)

Characterization, Cytotoxicity, and Genotoxicity of TiO2 and Folate-Coupled Chitosan Nanoparticles Loading Polyprenol-Based Nanoemulsion - Ran Tao; Chengzhang Wang; Changwei Zhang; WenJun Li; Hao Zhou; Hongxia Chen; Jianzhong Ye (Biological Trace Element Research, 2018)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

Investigation of Perfluoroalkyl Substances (PFASs) in Sediments from the Urban Lakes of Anqing City, Anhui Province, China - Fasong Li; Hanyu Huang; Zhibing Xu; Hui Ni; Hao Yan; Ran Chen; Yan Luo; Wei Pan; Jinyun Long; Xiaofang Ye; Xiaofen Qian; Guangming Yu (Bulletin of Environmental Contamination and Toxicology, 2017)

Genome-Wide QTL Analysis Identified Significant Associations Between Hypoxia Tolerance and Mutations in the GPR132 and ABCG4 Genes in Nile Tilapia - Hong Lian Li; Xiao Hui Gu; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2017)

Antioxidant capacity and identification of the constituents of ethyl acetate fraction from Rhus verniciflua Stokes by HPLC-MS - Hongxia Chen; Chengzhang Wang; Hao Zhou; Ran Tao; Jianzhong Ye; Wenjun Li (Natural Product Research, 2017)

Global mapping of artificial surfaces at 30-m resolution - XueHong Chen; Xin Cao; AnPing Liao; LiJun Chen; Shu Peng; Miao Lu; Jin Chen; WeiWei Zhang; HongWei Zhang; Gang Han; Hao Wu; Ran Li (Science China Earth Sciences, 2016)

COMP-Ang1 promotes long-term survival of allogeneic islet grafts in a bioinert perforated chamber by inhibiting inflammation via inhibition of the TLR4 signaling pathway - Dalei Wang; Lina Jiang; Yingzi Liang; Xiaoyan Hao; Chen Chen; Wei Xia; Ran Zhuang; Yingjun Su; Shuzhong Guo (Biotechnology Letters, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Endothelium-specific SIRT1 overexpression inhibits hyperglycemia-induced upregulation of vascular cell senescence - HouZao Chen; YanZhen Wan; Shuang Zhou; YunBiao Lu; ZhuQin Zhang; Ran Zhang; Feng Chen; DeLong Hao; Xiang Zhao; ZhiChen Guo; DePei Liu; ChihChuan Liang (Science China Life Sciences, 2012)

Involvement of recF in 254 nm Ultraviolet Radiation Resistance in Deinococcus radiodurans and Escherichia coli - Xiaosong Chang; Lan Yang; Qing Zhao; Wenjuan Fu; Hao Chen; Zhiqun Qiu; Ji-an Chen; Ran Hu; Weiqun Shu (Current Microbiology, 2010)

High prevalence of a novel porcine bocavirus in weanling piglets with respiratory tract symptoms in China - Shaolun Zhai; Cheng Yue; Zuzhang Wei; Jinxue Long; Duoliang Ran; Tao Lin; Yu Deng; Lv Huang; Lichang Sun; Haihong Zheng; Fei Gao; Hao Zheng; et al. (Archives of Virology, 2010)

Rapid Evolution, Genetic Variations, and Functional Association of the Human Spermatogenesis-Related Gene NYD-SP12 - Qü Zhang; Feng Zhang; Xiao-hua Chen; Yin-qiu Wang; Wei-qi Wang; Alice A. Lin; Luca L. Cavalli-Sforza; Li Jin; Ran Huo; Jia-hao Sha; Zheng Li; Bing Su (Journal of Molecular Evolution, 2007)